2017
DOI: 10.1016/j.molcel.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Accumulation of H3K27me3 on Nascent DNA Is Essential for Recruitment of Transcription Factors at Early Stages of Stem Cell Differentiation

Abstract: SUMMARY Recruitment of transcription factors (TFs) to repressed genes in euchromatin is essential to activate new transcriptional programs during cell differentiation. However, recruitment of all TFs, including pioneer factors, is impeded by condensed H3K27me3-containing chromatin. Single-cell and gene-specific analyses revealed that during the first hours of induction of differentiation of mammalian ESCs, accumulation of the repressive histone mark H3K27me3 is delayed after DNA replication, indicative of deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 46 publications
6
60
0
Order By: Relevance
“…We expect that the insights that emerge from our study may allow for a more precise analysis of the biological function of regions that display true intermediate methylation values in non-transformed cells. Finally, it remains to be seen whether the global lag of remethylation after replication has a biologically relevant role at some sites including, but not limited to, providing a window of opportunity for TFs to access their genomic targets 35 , as recently reported for H3K27me3 (Ref 36 ). In conclusion, our description of the genome-wide lag between the copying of genetic and epigenetic information adds further insight to our understanding of how epigenetic information is mitotically inherited.…”
Section: Discussionmentioning
confidence: 86%
“…We expect that the insights that emerge from our study may allow for a more precise analysis of the biological function of regions that display true intermediate methylation values in non-transformed cells. Finally, it remains to be seen whether the global lag of remethylation after replication has a biologically relevant role at some sites including, but not limited to, providing a window of opportunity for TFs to access their genomic targets 35 , as recently reported for H3K27me3 (Ref 36 ). In conclusion, our description of the genome-wide lag between the copying of genetic and epigenetic information adds further insight to our understanding of how epigenetic information is mitotically inherited.…”
Section: Discussionmentioning
confidence: 86%
“…Regulatory sequences containing CpG islands in promoters or intergenic regions are mostly unmethylated at all stages of development, but can be methylated if protective transcription factors are expressed less or not at all in one sex versus the other. Interestingly, Kdm6a, an X-linked histone lysine demethylase, plays an important role in establishing new transcriptional programs upon human and mouse ES cell differentiation [114] and is expressed more highly in female ES cells, [51] begging the question of whether it plays a role in later sexual dimorphisms via differential epigenomic modulation. However, DNA methylation might not be flexible enough to encode sex biases at early stages, whereas it could cement dimorphisms at differentiation end points.…”
Section: Which Epigenetic Modifications Are the Enduring Identifiers mentioning
confidence: 99%
“…Interestingly, many factors with repressive activity were found to be particularly sensitive to cell cycle changes. The repressor proteins may be critical to deposit repressive marks temporarily after DNA replication in S phase to prevent differentiation (Petruk et al, 2017), after which their levels need to be reduced again to enable plasticity. The same proteins that we identified here in whole cell lysates were recently found to be overrepresented in the chromatin-associated fraction of the mESC proteome (van Mierlo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported relatively uniform expression of pluripotency TFs during cell cycle both at mRNA and protein level (Shin et al, 2016;Singh et al, 2013), while others have revealed fluctuations (Gonzales et al, 2015;Van Der Laan et al, 2014;Tsubouchi et al, 2013). Given the interconnection between ESC fate choices and cell cycle (Gonzales et al, 2015;Jääger et al, 2019;Van Oudenhove et al, 2016;Pauklin and Vallier, 2013;Petruk et al, 2017), we aimed to map mESC proteome dynamics during cell cycle on a global scale.…”
Section: Proteome Dynamics In Pluripotent Cellsmentioning
confidence: 99%